Analysis and optimisation of reinforcing materials for wood adhesives - Vlastimil Buriánek; Petra Laciková (Acta Polytechnica CTU Proceedings, 2025)
Adhesives are very important in the field of glued timber elements. In recent years, more and more attention has been paid to innovations in the field of adhesives for wood materials. Not only in terms of mechanical properties but also in terms of environmental aspects. Wood remains a popular material in the construction industry, but the challenge remains how to ensure the long-term stability and durability of its glued joints. The designed elements must withstand various changes of moisture as well as elevated temperatures throughout the lifetime of the structure. Optimising wood adhesives through appropriate fillers or fibres selection is a step towards more sustainable building materials. The aim of the work was to select suitable fillers or fibres for adhesives based on optimisation through the pairwise comparison method. According to the results obtained, glass (99.98 %) and carbon (95.92 %) fibres can be considered as the most suitable reinforcement material. Basalt fibres, nanocellulose and montmorillonite particles achieved an average of 56 %. TiO2, SiO2 and Al2O3 particles can be considered as unsuitable fillers for adhesives based on the weight of the selected criteria.